Investigating the effect of exercise on the expression of genes related to cardiac physiological hypertrophy: Exercise and cardiac physiological hypertrophy genes - Xiong, Yunhui; Wang, Juan; Huang, Shuxia; Cao, Yizhong (Cellular and Molecular Biology, 2023)
Physiological hypertrophy of the heart is associated with an increase in the normal function of the heart, and it directly relates to regular exercise, especially among elite athletes. Researches about special signaling pathways that create physiological hypertrophy have recently received more attention. As a result, the present study was conducted to investigate the effect of aerobic exercise intensity on the expression of genes involved in heart physiological hypertrophy. For this purpose, 30 male Wistar rats were prepared and randomly divided into three groups: control, intense intermittent training, and submaximal continuous training. The intensive intermittent training protocol included 30 minutes of intermittent running, each interval including 4 minutes of running with an intensity of 85-90% VO2max and 2 minutes of active recovery with an intensity of 50-60% VO2max three days a week for 8 weeks. Also, the submaximal continuous exercise group had activity intensity equal to 50-55% of the maximum oxygen consumption. The expression of genes related to cardiac hypertrophy such as MMP-I, TGF-ß1, and TIMP was evaluated through real-time PCR technique. The results showed that the expression of studied genes in the three groups had significant differences (p<0.05). Both training methods led to a significant increase in TGF-ß1 and TIMP gene expression in the heart of rats. But the changes in MMP-I in the intermittent group were not significant compared to the control group. In general, it seems that exercise leads to the improvement of the factors involved in the physiological hypertrophy of the heart. Therefore, the findings of the current research are expressed with caution and more research is needed in the future.